Do Jet Fuel Price Movements Help Forecast Airline Fares and the Demand for Air Travel? - Atems, Bebonchu; Bachmeier, Lance J.; Williams, Corey (My University, 2018)
The paper studies the predictive content of jet fuel prices for the U.S. aviation industry through in-sample and out-of-sample forecasting exercises. Our results suggest the possibility of limited improvements in the predictions of airline fares, and little evidence of predictability from jet fuel prices to measures of air travel demand.
Citation: Bebonchu, A., Bachmeier, L., & Williams C. (2018) Do Jet Fuel Price Movements Help Forecast Airline Fares and the Demand for Air Travel? Unpublished manuscript.
Keywords: Q41; C32; Jet fuel; out-of-sample forecasting; Airline industry